INTERNALISASI NILAI-NILAI KARAKTER MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - HERNI ALISKA (STIT DARUL ULUM KOTABARU, 2023)
This article aims to explain the internalization of character values through learning Islamic religious education. The type of writing used is a literature review study that focuses on writing results related to writing topics or variables. The data used in this study comes from research results that have been conducted and published in national and international online journals. The analytical method used is journal content analysis. The results of the study show that: (1) Instilling religious character values in students through congregational noon prayers and the habit of reading the Al-Quran before starting learning; (2) Internalization of Discipline Character Values​in Islamic Religious Education Learning, namely the noon prayer in congregation, 5S activities are activities that emphasize the disciplinary aspects of school rules, while the habit of reading the Al-Qur'an Juz Amma before the start of learning this activity emphasizes the disciplinary aspects class; (3) Internalization of the Character Value of Hard Work in Islamic Religious Education Learning in schools through the habit of dhikr and memorization. All of these activities allow students to take responsibility and work hard as assigned by the teachers/ustdzah.